GAYA KEPEMIMPINAN ADAPTIF KEPENGHULUAN DALAM MENDORONG PENGELOLAAN BUMKep DI KEPENGHULUAN MENGGALA SEMPURNA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR TAHUN 2024 - Ristanti, Yunda; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Indonesia's national development emphasizes empowering local potential through village-based development or village governance. Within this framework, Village-Owned Enterprises (BUMKep) play a strategic role as community economic institutions to increase local independence and prosperity. This study aims to analyze the adaptive leadership style of the village head in managing the BUMKep (Village-Owned Enterprise) in the Menggala Sempurna Village, Tanah Putih District, Rokan Hilir Regency, in 2024, and to identify the driving and inhibiting factors. This study used a qualitative method with a descriptive approach through in-depth interviews, observation, and documentation. The results show that the village head's adaptive leadership is seen through adjusting the BUMKep management strategy to the community's socio-economic changes, building collaboration with local government and community leaders, and encouraging community participation in developing business units based on local potential. Factors driving the implementation of adaptive leadership include high community trust in the village head, support from village officials and local resource potential, and the village head's willingness to continue learning and establishing communication with various stakeholders. However, its implementation has not been optimal due to: (1) limited managerial capacity of BUMKep administrators, (2) weak governance, particularly in terms of transparency and accountability, and (3) limited capital and access to financing. Therefore, increased management capacity, transparent and accountable governance, and financial support are needed to promote the economic independence of village heads. Keywords: Adaptive Leadership, Village Heads, Bumkep, Governance, Empowerment Local Economy